2017
DOI: 10.21613/gorm.2016.633
|View full text |Cite
|
Sign up to set email alerts
|

Total Blood Lymphocyte Count Alteration During and after Pregnancy

Abstract: OBJECTIVE:To investigate the impact of gestational changes on blood lymphocyte count in healthy pregnancies. STUDY DESIGN:This retrospective study is consisted of 108 consecutive normal pregnancies who delivered at our department in December 2015. High-risk pregnancies with poor neonatal outcome and pregnancies with maternal disorders which may affect lymphocyte counts were excluded from the study. "Complete blood count" results of the patients were obtained from the computerized data base system of Hacettepe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Some older papers suggest that there was no change overall in lymphocyte count during pregnancy (13,14). Results from more recent studies suggest that there is a decrease in lymphocyte count (15,16), with the biggest decrease occurring in the first and second trimesters (5). The bulk of available literature agrees with the findings of a reduction in overall lymphocyte count; however, a recent study in 2013 found a significant increase in the lymphocyte count of 200 pregnant women (17,18), further complicating the discussion.…”
Section: Discussionmentioning
confidence: 69%
“…Some older papers suggest that there was no change overall in lymphocyte count during pregnancy (13,14). Results from more recent studies suggest that there is a decrease in lymphocyte count (15,16), with the biggest decrease occurring in the first and second trimesters (5). The bulk of available literature agrees with the findings of a reduction in overall lymphocyte count; however, a recent study in 2013 found a significant increase in the lymphocyte count of 200 pregnant women (17,18), further complicating the discussion.…”
Section: Discussionmentioning
confidence: 69%
“…Women with iron stores have a smaller increase than those with iron deficiency. This inability to expand plasma volume may disguise a decrease in hemoglobin content in some iron-deficient women (40).…”
Section: Biochemical Alterations Of the Study Populationmentioning
confidence: 99%